2005
DOI: 10.1158/0008-5472.can-04-3398
|View full text |Cite
|
Sign up to set email alerts
|

Functional Loss of the γ-Catenin Gene through Epigenetic and Genetic Pathways in Human Prostate Cancer

Abstract: Abstract;-Catenin is a cell adhesion molecule and a candidate mediator of Wnt signal transduction. We hypothesized that impaired regulation of ;-catenin through genetic and epigenetic pathways is associated with the pathogenesis of prostate cancer. To test this hypothesis, cytosine-phosphate-guanine methylation, loss of heterozygosity (LOH), and mutation status of the g g-catenin gene were analyzed in cultured prostate cancer cell lines, 180 localized prostate cancers, 69 benign prostatic hyperplasias, and 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…This would be consistent with data implicating plakoglobin in the development of squamous cell carcinoma through induction of Bcl-2 (Hakimelahi et al, 2000). Nuclear accumulation of plakoglobin and an increase in Bcl-2 expression has also been observed in advanced prostate cancer (Shiina et al, 2005). However, other evidence suggests that plakoglobin functions as a tumour suppressor with loss of heterozygosity being linked to poor clinical outcomes in breast, ovarian and small cell lung cancers (Aberle et al, 1995;Winn et al, 2002).…”
Section: Desmosomes and Apoptosis In Rnd3-depleted Cellssupporting
confidence: 86%
“…This would be consistent with data implicating plakoglobin in the development of squamous cell carcinoma through induction of Bcl-2 (Hakimelahi et al, 2000). Nuclear accumulation of plakoglobin and an increase in Bcl-2 expression has also been observed in advanced prostate cancer (Shiina et al, 2005). However, other evidence suggests that plakoglobin functions as a tumour suppressor with loss of heterozygosity being linked to poor clinical outcomes in breast, ovarian and small cell lung cancers (Aberle et al, 1995;Winn et al, 2002).…”
Section: Desmosomes and Apoptosis In Rnd3-depleted Cellssupporting
confidence: 86%
“…Another suggestion is that plakoglobin causes unregulated growth and foci formation (in human squamous carcinoma cells), as a result of induction of the pro-survival gene Bcl-2 and inhibition of apoptosis (Hakimelahi et al, 2000). In support of the latter idea, mutations within or near to a glycogen synthase kinase-3b consensus phosphorylation site have been discovered in advanced hormone refractory prostate cancer, and these coincide with strong nuclear accumulation of plakoglobin and a concomitant increase in Bcl-2 (Shiina et al, 2005). By contrast, in early prostate cancer, it appears to be loss of expression of plakoglobin, as a result of loss of heterozygosity (LOH) and hypermethylation of the plakoglobin promoter, that is important (Shiina et al, 2005).…”
Section: Plakoglobin and Cancermentioning
confidence: 97%
“…Prior studies have shown that DNA hypermethylation is a crucial mechanism in transcriptional silencing of tumor-related genes in PCa. (6,7) The retinoblastoma protein-interacting zinc finger gene, RIZ1, was isolated with a functional screen for retinoblastoma (Rb)-binding proteins.(8) Domain analysis suggested that RIZ1 is a histone methyltransferase (HMT) specific for the lysine 9 residue of histone H3, an activity known to be linked with transcriptional repression.(9) RIZ1 is considered to be a tumor suppressor gene because it can induce G 2 -M arrest and apoptosis of several types of cancer cells.(10,11) RIZ1 plays an important role in human cancers, as evidenced by genetic mutations. (12)(13)(14) The RIZ1 gene is located on human chromosome 1p36, a region deleted in many human cancers, (15) and chromosome 1p36 is a potential hereditary PCa susceptibility locus.…”
mentioning
confidence: 99%
“…Prior studies have shown that DNA hypermethylation is a crucial mechanism in transcriptional silencing of tumor-related genes in PCa. (6,7) The retinoblastoma protein-interacting zinc finger gene, RIZ1, was isolated with a functional screen for retinoblastoma (Rb)-binding proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation